Educação sexual: construção coletiva de um plano de ação com adultos de referência no espaço escolar - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The study presents an innovative proposal to promote Sexual Education in schools, based on the collective construction of an action plan involving reference adults, such as teachers and parents, with the aim of transforming the school environment into a safer and more informed space about sexuality. Through action research conducted in a public school in the metropolitan region of Porto Alegre, 32 teachers and 12 parents participated. The results show that, although there is recognition of the importance of Sexual Education, most teachers did not receive specific training and initiatives at schools are still limited. Parents, on the other hand, see dialogue about sexuality as essential, but have different perceptions of the subject. The research highlights the need for teacher training, greater integration between school and family, and suggests strategies such as joint training and inter-institutional partnerships to strengthen the teaching of Sexual Education in a safe, participative, and informed way.
Sex education: developing a collaborative action plan with school-based reference adults
Keywords: Educação Sexual; Action research; School setting; Teacher training; School-family dialogue; Espaço escolar; Sexual Education; Diálogo escola-família; Pesquisa-ação; Formação docente; CIENCIAS HUMANAS